Researching Navigation of Project Complexity Using Design Science Research - Venable, John; Mikkelsen, Mogens Frank (2019)
Project complexity is becoming increasingly challenging for project managers. Much research has been done on the concept of project complexity. However, not enough has been done on developing and providing guiding principles for navigation of project complexity. Using action design research, this paper presents the design for and evaluation of a conceptual artefact (the “Complexity Navigation Window”) to contribute toward a user interface for a decision support system (DSS) for project management. The designed artefact has been through a process of formative evaluation with indication of a high degree of relevance and utility of the artefact for 16 practitioners of project management. The contributions of the paper are improved understanding of practitioners’ perceptions of project complexity and design of navigation principles for managing the project complexity, for which the paper presents four strategies. The paper also provides a methodological discussion of Action Design Research, which is not often used in research on project management.